In the way : indigenous peoples, life projects, and development - Blaser, Mario, 1966-; Feit, Harvey A.; McRae, Glenn (Zed Books in association with International Development Research Centre, Ottawa ; Distributed exclusively in the U.S. by Palgrave, 2004)
Indigenous peoples today are enmeshed in the expanding modern economy, subject to the pressures of both market and government. This book takes indigenous peoples as actors, not victims, as its starting point in analysing this interaction. It assembles a rich diversity of statements, case studies and wider thematic explorations, primarily from North America, and particularly the Cree, the Haudenausaunee (Iroquois) and Chippewa-Ojibwe peoples who straddle the US/Canadian border, but also from South America and the former Soviet Union. It explores the complex relationships between indigenous peop.